Пути повышения работоспособности выталкивающего устройства коксовыталкивателя - Рындяев, В. И. (НТУ "ХПИ", 2015)
Создание выталкивающего устройства, основные параметры и конструктивные решения которого обеспечивают повышенный уровень работоспособности за счет снижения нетехнологических нагрузок, является актуальной задачей. Исследовано выталкивающее устройство коксовыталкивателя. Изучено формирование величины эквивалентных нагрузок с учетом слеживаемости кокса. Проанализировано влияние конструктивных решений выталкивающего устройства на снижение уровня действующих нагрузок.

Investigated eject mechanism coke pusher. The reasons of equipment failure. It was established that the main cause of failure is high tension parts of the devices due to the increased power parameters of the process and significant dynamic loads. It was found that the main failure modes are fatigue failures. Classified load acting ejectors. Studied the formation of the equivalent loads considering caking coke. Develop criteria for assessing schemes ejecting pusher. The most important criteria for evaluating the schemes ejecting pusher are: 1. Kritery ensure process parameters and product quality indicators. 2. Kritery performance: - a margin of safety for maximum loads; - a margin of safety for the equivalent load; - the dynamic criterion; 3. Ekonomichesky criterion Criteria for the process parameters and quality indicators is the starting product, monitors compliance with the developed scheme of the device. The notion of "efficiency" is qualitative, and to evaluate the performance values are used margin of safety.Analyzed the impact of design decisions ejecting at reducing operating loads.
Ways to improve performance ejecting pusher
Keywords: коксохимическое производство; динамические нагрузки; конструкции; слеживаемость кокса; drive; schematics; transmission